Effect of Intellectual, Emotional, and Spiritual Intelligence on Employee Performance at State Owned Company: A Quantitative Study - Enkky Sasono Sasono Wijaya; Voni Lestari; Mardi; Osly Usman (Communications of International Proceedings, 2022)
The purpose of this study is to see if there is a link between intellectual intelligence, emotional intelligence, and spiritual intelligence and employee performance at State Owned Company The quantitative approach was used in this study. The population in this study was employees at PT Fio Amanah Perdana, with 126 respondents sampled using a random sampling technique based on the Slovin formula, yielding 100 sample respondents. Data collection via online questionnaires distributed via Google Forms. The SEM PLS software application is used in the data analysis technique (Structural Partial Equation Modeling Least squares). The findings revealed a significant relationship between the variables of intellectual intelligence and spiritual intelligence and employee performance at State owned Company, the emotional intelligence variable has no effect on employee performance.
Keywords: Intellectual Intelligence; Emotional Intelligence; Spiritual Intelligence; Employee Performance